2019
DOI: 10.3892/ijo.2019.4725
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and its low calcemic analogs modulate the anticancer properties of cisplatin and dacarbazine in the human melanoma A375 cell line

Abstract: Melanoma represents a significant challenge in cancer treatment due to the high drug resistance of melanomas and the patient mortality rate. This study presents data indicating that nanomolar concentrations of the hormonally active form of vitamin D, 1α,25-dihydroxyvitamin D3 [1α,25(OH)2D3], its non-calcemic analogues 20S-hydroxyvitamin D3 and 21-hydroxypregnacalciferol, as well as the low-calcemic synthetic analog calcipotriol, modulate the efficacy of the anticancer drugs cisplatin and dacarbazine. It was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 98 publications
2
27
0
Order By: Relevance
“…It is worth mentioning that CP can promote ROS levels in mediating cell death in cancer cells. However, when an anti-tumor agent, such as vitamin D is co-administered with CP, its potential in enhancing ROS levels enhances [234]. Furthermore, a combination of CP with other anti-tumor compounds provide conditions for suppressing molecular pathways that can enhance cancer progression.…”
Section: Therapeutic Targetingmentioning
confidence: 99%
“…It is worth mentioning that CP can promote ROS levels in mediating cell death in cancer cells. However, when an anti-tumor agent, such as vitamin D is co-administered with CP, its potential in enhancing ROS levels enhances [234]. Furthermore, a combination of CP with other anti-tumor compounds provide conditions for suppressing molecular pathways that can enhance cancer progression.…”
Section: Therapeutic Targetingmentioning
confidence: 99%
“…Furthermore, as revealed by analysis of transcriptome of melanoma patients, VDR expression was independently protective for melanomarelated death in both primary and metastatic disease (27). What is more, it was shown that active forms of vitamin D improve efficacy of several anticancer drugs, such as cisplatin (28,29), dacarbazine (30), doxorubicin (31), and proton therapy (32). It is also suggested that vitamin D immune-modulating ability could offer indications for a novel vitamin D application in melanoma patients receiving immunotherapy (33).…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall response rate to DTIC rarely exceeds 17.6% ( 4 , 5 ). Mechanistically, DTIC is an alkylating agent that promotes G 1 -phase cell cycle arrest ( 6 ). Alkylating agents favor the formation of O6-alkylguanine derivatives, which bind to thymine instead of cytosine during DNA replication, thereby blocking cell division and causing cell death at the G 1 and S phases ( 7 ).…”
Section: Introductionmentioning
confidence: 99%